1 - Introduction: The Contradictions and Ironies of Elections in Africa: by Kwame A. Ninsin - Ninsin, Kwame A. (Africa Development, 2006)
This introduction interrogates the popular meaning attached to elections in a liberal democracy, where they are generally regarded as expressing the political and civil rights of the citizens. It argues that contrary to this popular view, elections in Africa have become arenas where the elite contest for the consent of the people to exercise state power. The people on their part perceive elections as the entry for securing development projects to improve their material conditions. To this end, the elite employ various mechanisms such as intimidation, election fraud, and primordial identities like tribe and religion to bend election outcomes in their favour. Added to these is poverty, which is employed by the elite to reduce the people to dependency within the framework of clientelism. The result is that elections in Africa tend to confer popular consent on the exercise of state power, but only in the formal sense; in reality elections produce ‘choiceless democracies’.